Mobile and Wireless Technologies 2017 ICMWT 2017 (Lecture Notes in Electrical Engineering,, 2018)
This book gathers the proceedings of the 4th International Conference on Mobile and Wireless Technology (ICMWT), held in Kuala Lumpur, Malaysia in June 2017, an event that provides researchers and practitioners from both academia and industry with a platform to keep them abreast of cutting-edge developments in the field. The peer-reviewed and accepted papers presented here address topics in a number of major areas: Mobile, Wireless Networks and Applications; Security in Mobile and Wireless; Mobile Data Management and Applications; Mobile Software; Multimedia Communications; Wireless Communications; and Services, Application and Business. .